Charitable giving and nonbinding contribution-level suggestions: Evidence from a field experiment - Maja Adena; Steffen Huck; Imran Rasul (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
When asking for donations, charitable organizations often use suggestions concerning the amount of potential contributions. However, the evidence concerning the effects of such suggestions is scarce and inconsistent. Unlike the majority of existing studies concerned with small-money solicitations, we examine the effect of larger nonbinding suggestions in the context of middle-range donations which are relevant in practice. In our randomized field experiment, opera visitors received solicitation letters asking to support a social youth project organized by the opera house. The three different treatments were: no suggestion and suggestions of exteuro100 and exteuro200, respectively. Both suggestions were larger than average and median donations in this context. The findings are that suggestions substantially influence the distribution of donations received. The mean amounts given increase significantly if a suggestion is made. The increase is stronger in the exteuro200 treatment. On the other hand, the participation rate decreases if a suggestion is made. Overall, the returns from the campaign increase non-significantly when a suggestion is made. The solicitation was repeated a year later, without any suggestion. There is weak evidence that suggestions have a long-term effect on individual contribution-level decisions. – – Karitative Organisationen suggerieren oft den Spendern eine bestimmte Beitragshöhe. Allerdings wissen wir wenig über die Wirkung solcher Empfehlungen. Es gibt wenig Literatur zu dem Thema und die Aussagen sind auch nicht immer konsistent. Wir untersuchen die Wirkung einer Spendenempfehlung in dem Kontext mittlerer Spenden, die in der Praxis relevanter sind als die Kleinspenden, die im Zentrum bisheriger Literatur lagen. In unserem randomisierten Feldexperiment haben Opernbesucher Anfragebriefe erhalten mit einer Bitte das Sozialprojekt der Oper für Kinder und Jugendliche zu fördern. Die drei unterschiedliche Treatments waren: keine Empfehlung, eine Empfehlung von 100 sowie 200 Euro. Der empfohlene Beitrag wurde so gewählt, dass er über dem aus ähnlichen Kampagnen bekanntem Durschnitt bzw. Median lag. Die Ergebnisse zeigen, dass die Empfehlungen die Verteilung der Spenden stark beeinflussen. Die durchschnittliche positive Spende ist höher mit Empfehlung. Der Anstieg ist größer, wenn 200 Euro suggeriert werden. Andererseits wird seltener gespendet im Fall einer Empfehlung. Die Spendeneinnahmen aus der Kampagne steigen insgesamt mit der Empfehlung, allerdings nicht signifikant. Die Teilnehmer erhielten eine weitere Spendenanfrage ohne Empfehlung ein Jahr später. Es zeigt sich, dass die Empfehlungen auch eine Langzeitwirkung auf die Entscheidung bezüglich der Spendenhöhe haben.
Keywords: C93; D12; D64; 330; Charitable giving; Field experiment; Suggestions